A Plasmodium homolog of ER tubule‐forming proteins is required for parasite virulence. Issue 3 (19th June 2020) - Shi, Xiaoyu; Hai, Lei; Govindasamy, Kavitha; Gao, Jian; Coppens, Isabelle; Hu, Junjie; Wang, Qian; Bhanot, Purnima
Abstract: Reticulon and REEP family of proteins stabilize the high curvature of endoplasmic reticulum (ER) tubules. Plasmodium berghei Yop1 ( Pb Yop1) is a REEP5 homolog in Plasmodium . Here, we characterize its function using a gene‐knockout ( Pb yop1∆). Pb yop1∆ asexual stage parasites display abnormal ER architecture and an enlarged digestive vacuole. The erythrocytic cycle of Pb yop1∆ parasites is severely attenuated and the incidence of experimental cerebral malaria is significantly decreased in Pb yop1∆‐infected mice. Pb yop1∆ sporozoites have reduced speed, are slower to invade host cells but give rise to equal numbers of infected HepG2 cells, as WT sporozoites. We propose that Pb YOP1's disruption may lead to defects in trafficking and secretion of a subset of proteins required for parasite development and invasion of erythrocytes. Furthermore, the maintenance of ER morphology in different parasite stages is likely to depend on different proteins. Abstract : Pb YOP1 is a putative ER‐shaping protein in the malaria parasite, Plasmodium . Parasites lacking Pb YOP1 ( Pb yop1Δ) have malformed ER and enlarged digestive vacuoles, and are severely attenuated during growth in the mammalian host.